2017
DOI: 10.2196/mental.6921
|View full text |Cite
|
Sign up to set email alerts
|

Peer Communication in Online Mental Health Forums for Young People: Directional and Nondirectional Support

Abstract: BackgroundThe Internet has the potential to help young people by reducing the stigma associated with mental health and enabling young people to access services and professionals which they may not otherwise access. Online support can empower young people, help them develop new online friendships, share personal experiences, communicate with others who understand, provide information and emotional support, and most importantly help them feel less alone and normalize their experiences in the world.ObjectiveThe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 40 publications
(85 reference statements)
8
92
2
5
Order By: Relevance
“…Interaction influenced knowledge and behavior related to health (including risk taking and health protection) and relationships as well as the migration experience. Our results, which resonate with findings from other research found this forum to be a strong resource for support and information [39,[64][65][66], including in the context of online peer based interventions to trial the provision of mental and sexual health promotion (also conducted by members of our research team) targeting same sex attracted young people and adult men who have sex with men [29]. Further exploration of the role of peer support in this context via a formal online outreach intervention may be warranted.…”
Section: Comparison With Prior Worksupporting
confidence: 91%
See 1 more Smart Citation
“…Interaction influenced knowledge and behavior related to health (including risk taking and health protection) and relationships as well as the migration experience. Our results, which resonate with findings from other research found this forum to be a strong resource for support and information [39,[64][65][66], including in the context of online peer based interventions to trial the provision of mental and sexual health promotion (also conducted by members of our research team) targeting same sex attracted young people and adult men who have sex with men [29]. Further exploration of the role of peer support in this context via a formal online outreach intervention may be warranted.…”
Section: Comparison With Prior Worksupporting
confidence: 91%
“…This advice and support was both directive (practical advice) and non-directive (sharing personal experiences) [39] and in particular focused on informational and emotional support. While many users may have initially joined the forum seeking information, participation continued due to the relationships formed with other members.…”
Section: Principal Resultsmentioning
confidence: 99%
“…Often the disclosures from group members were detailed and offered a lot of personal information, similar to recent findings relating to online blogs [70], indicating that the poster felt that they were in a safe place to discuss their experiences. This is indicative of a sense of group cohesion, and is supportive of further research findings [27,34].…”
Section: Principle Findingssupporting
confidence: 84%
“…Findings suggest it is a valuable platform for sharing personal experiences of mental illness, increasing the individuals' perception of the level of social support they received [74,75] in addition to support gained from family, friends and professionals. By sharing personal experiences of their mental illness, Facebook users provided informational and emotional support to other group members that may not be available from the receivers own social network or professionals, in line with previous research [18,19,34]. This form of support may lead to increased feelings of connectedness for the receiver [67,78], and could potentially reduce feelings of social isolation [22][23][24]74], and may offer hope to people using Facebook for their mental illness [76], thus empowering them to seek help or take positive action.…”
Section: Principle Findingssupporting
confidence: 59%
See 1 more Smart Citation